Multi-pathogen infections and Alzheimer's disease - Vigasova, Dana; Nemergut, Michal; Liskova, Barbora; Damborsky, Jiri (Microbial cell factories, 2021)
Alzheimer's disease (AD) is a chronic neurodegenerative disease associated with the overproduction and accumulation of amyloid-β peptide and hyperphosphorylation of tau proteins in the brain. Despite extensive research on the amyloid-based mechanism of AD pathogenesis, the underlying cause of AD is not fully understood. No disease-modifying therapies currently exist, and numerous clinical trials have failed to demonstrate any benefits. The recent discovery that the amyloid-β peptide has antimicrobial activities supports the possibility of an infectious aetiology of AD and suggests that amyloid-β plaque formation might be induced by infection. AD patients have a weakened blood-brain barrier and immune system and are thus at elevated risk of microbial infections. Such infections can cause chronic neuroinflammation, production of the antimicrobial amyloid-β peptide, and neurodegeneration. Various pathogens, including viruses, bacteria, fungi, and parasites have been associated with AD. Most research in this area has focused on individual pathogens, with herpesviruses and periodontal bacteria being most frequently implicated. The purpose of this review is to highlight the potential role of multi-pathogen infections in AD. Recognition of the potential coexistence of multiple pathogens and biofilms in AD's aetiology may stimulate the development of novel approaches to its diagnosis and treatment. Multiple diagnostic tests could be applied simultaneously to detect major pathogens, followed by anti-microbial treatment using antiviral, antibacterial, antifungal, and anti-biofilm agents.
Keywords: Alzheimerova nemoc; Infectious burden; Pathogens; Antifungal; lidé; Humans; Bacteria; Animals; Antibacterial; Biofilms; Alzheimer’s disease; zvířata; Antiviral; Anti-Infective Agents; Antiviral Agents; antivirové látky; Parasites; Viruses; Alzheimer Disease; antiinfekční látky; Anti-biofilm; biofilmy